Sintering temperature study on structure, magnetic properties and magnetoresistance of Pr0.67Ba0.33MnO3 - Wong, Jen Kuen; Lim, Kean Pah; Shaari, Abdul Halim; Chen, Soo Kien; Ng, S. W. (American Institute of Physics, 2009)
Polycrystalline perovskite manganite of Pr0.67Ba0.33MnO3 (PBMO) bulk ceramic samples were prepared by conventional solid‐state reaction method. The structures, typical magnetic properties and magnetoresistance were studied. At lower sintering temperature (900 °C to 1100 °C), formation of PBMO phase accompany by secondary phases of BaMnO3 and Pr6O11 were observed. However, at 1200 °C, pure single phase of PBMO was obtained. PBMO compounds become denser upon the increase in sintering temperature. A reduction of secondary phases as sintering temperature increased lead to the enhancement of magnetization value. The highest room temperature %MR of 17.1% was found in sample sintered at 1200 °C in 10 kG external magnetic field. In summary, higher sintering temperature reduced multiphase formation and enhanced the magnetic and magnetoresistance properties.